Asynchronous Message Handling in Modern Distributed Systems: Strategies for Enhanced Data Integrity - Vignesh Kuppa Amarnath (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Asynchronous message handling remains a critical challenge in distributed systems, particularly when addressing data loss prevention during system failures. This article presents a comprehensive analysis of strategies for implementing resilient message storage and processing mechanisms across distributed architectures. By examining the interplay between message queues, event-driven systems, and durable message brokers, this article demonstrates how proper implementation of these patterns can significantly enhance system reliability. This article explores key approaches including message replication, acknowledgment protocols, and transactional logging, while considering their impact on system performance and consistency. Through real-world case studies and practical implementations, it identifies optimal patterns for handling message persistence, recovery, and reprocessing across various failure scenarios. The findings suggest that carefully designed asynchronous messaging systems can achieve both high availability and data integrity, even under adverse conditions. This article contributes to the growing body of knowledge on distributed systems reliability by providing concrete strategies for architects and developers to implement robust message handling systems that balance performance requirements with data loss prevention guarantees.